Seneca l’insostituibile: il "Tieste" - Francesco Carpanelli (Il castello di Elsinore, 2013)
The paper aims to underline Seneca’s value, as a playwright, in the Ancient Theatre studies. After decades of bias against the value of his dramatic works, in order to make him a cento’s poet, we made the choice to analyze the Thiestes, as it is the only plot left of this family’ saga on the borderline of horror. The originality of the paper consists in two elements: the first one is the attempt to demonstrate how impossible it is to consider the Thyestes as the product of a patchwork of various Greco-romans authors, since all the fragments (from Sophocles to Accius) prove themselves not appropriate for a comparison, because of internal limits (with exception of Accius’ ones which might derive from a common source). The second element tries to underline – through a particular deconstruction of the lines – the unvarying and monolithic role of Atreus, which is anticipated by the Fury and supported by the Messenger’s account, a long monologue in which his demonic role subverts the entire dramatic distribution.